The Inspector general [videorecording (DVD)]. - Kaye, Danny; Slezak, Walter, 1902-1983; Lanchester, Elsa, 1902-1986; Gogolʹ, Nikolaĭ Vasilʹevich, 1809-1852 (Alpha Video Distributors, 2003)
A corrupt mid-nineteenth century Russian village wrongly suspects the assistant of a medicine-show operator of being Napoleon's omnipotent Inspector General in disguise.